2015
DOI: 10.1166/jnn.2015.10430
|View full text |Cite
|
Sign up to set email alerts
|

Glycothermal Synthesis and Photocatalytic Properties of Highly Crystallized Anatase TiO<SUB>2</SUB> Nanoparticles

Abstract: Highly crystallized anatase TiO2 nanoparticles were synthesized at a temperature as low as 120 °C through a glycothermal reaction using amorphous titanium hydrous gel as precursor and 1,4-butanediol and water as solvent. X-ray diffraction (XRD) and transmission electron microscopy (TEM) data support that the glycothermal processing method provides a simple low-temperature route for producing highly crystallized anatase TiO2 nanoparticles without pH adjustment. It is demonstrated that the shape and dispersabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In recent years, many researchers have studied photocatalysis using powder 7,8 or thin film 9–11 titania. Powder titania has a wider application because of its high specific surface area, quantum yield, and photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have studied photocatalysis using powder 7,8 or thin film 9–11 titania. Powder titania has a wider application because of its high specific surface area, quantum yield, and photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The diffractograms of pure and Mg-doped TiO 2 nanoparticles (0.75 and 1.5 at.%) are shown in Figure 1. It is obvious from the patterns, the anatase phase is the main phase in all samples [25]. However, a weak diffraction peak along (1 1 0) indicating the rutile phase is observed for pure titania showing the formation of a mixed phase structure for this sample.…”
Section: X-ray Diffractionmentioning
confidence: 79%
“…To synthesize crystalline particles using the glycothermal concepts embodied in hydrothermal processing approaches, a few investigations have studied the use of nonaqueous systems as glycol media. We have shown that a glycothermal process provides a facile low-temperature route to produce BaTiO 3 , Fe 3 O 4 , Y-doped ZrO 2 , TiO 2 , ZnO, and ZnS particles with the desired morphology and size, as described in our previous study [35][36][37][38][39][40][41]. Our research embodies some novelty concepts that differ from the reported technology for particle synthesis.…”
Section: Introductionmentioning
confidence: 80%
“…This result was consistent with the FT-IR analyses, as shown in Figure 9. The weak band at 1640 cm −1 , between 3600 cm −1 and 4000 cm −1 (bending mode of H 2 O), indicates that some H 2 O is present [38,39]. The two broad peaks at around 750 cm −1 and 3350 cm −1 are associated with the O-H stretching vibration of absorbed water and hydroxyl group [27,38,39].…”
Section: Glycothermal Synthesis Of Knn Particlesmentioning
confidence: 99%